2020
DOI: 10.2147/ott.s244525
|View full text |Cite
|
Sign up to set email alerts
|

<p>Down-Regulation of ZEB1 by miR-199a-3p Overexpression Restrains Tumor Stem-Like Properties and Mitochondrial Function of Non-Small Cell Lung Cancer</p>

Abstract: Objective: ) targeting of 3ʹ-UTR of ZEB1 was characterized as an important way to inhibit invasion and metastases in nonsmall cell lung cancer (NSCLC), one of the most common cancers around the world. Here we aimed to investigate the tumor-suppressive role of miR-199a-3p targeted ZEB1. Materials and Methods: A549 cells were transfected with ZEB1 and/or miR-199a-3p. Then, tumor growth was investigated in xenograft mice. Stem-like property, proliferation and mitochondria injury were further validated in vitro. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Furthermore, AGR2 forced expression almost abolished the inhibitory effect of miR-199a-3p on LUAD cell proliferation and apoptosis. In addition to our findings, Bai et al demonstrated that the upregulation of miR-199a-3p inhibited ZEB1 expression in lung cancer cells and further confirmed this effect in xenograft mice [ 20 ]. MiR-199a-3p is considered to target different genes to interfere with the progression of lung cancer.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, AGR2 forced expression almost abolished the inhibitory effect of miR-199a-3p on LUAD cell proliferation and apoptosis. In addition to our findings, Bai et al demonstrated that the upregulation of miR-199a-3p inhibited ZEB1 expression in lung cancer cells and further confirmed this effect in xenograft mice [ 20 ]. MiR-199a-3p is considered to target different genes to interfere with the progression of lung cancer.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, there is increased expression of miR-199a-3p in patients with lung cancer, and this miRNA could serve as a biomarker for diagnosing lung cancer [ 36 , 37 ]. Bai et al demonstrated that the upregulation of miR-199a-3p inhibited ZEB1 inhibited lung cancer growth in vitro and in vivo [ 20 ]. Therefore, miR-199a-3p plays a tumor-suppressing role during cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study suggested that miR-199a-3p overexpression halted the carcinogenesis process of esophageal squamous cell carcinoma [36]. In non-small cell lung cancer, miR-199a-3p was found to inhibit stemness and induce mitochondria dysfunction-mediated apoptosis of A549 cells via targeting ZEB1 [37]. Similarly, this study found that the expression level of miR-199a-3p in Ewing's sarcoma tissues and cell lines was significantly lower than that in adjacent non-tumorous tissues and human normal osteoblast cell line, and overexpression of miR-199a-3p could inhibit Ewing's sarcoma cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…A research reported that cerebral microvascular endothelial cells displayed less apoptosis levels through microRNA-199b-3p via downregulating MAPK/ERK/EGR1 axis in ischemic stroke [ 14 ]. In addition, microRNA-199b-3p upregulation induced apoptosis mediated by mitochondria pathway through targeting ZEB1 [ 28 ]. Then, MAPK pathway was further investigated in hippocampus neurons under OGD conditions where mmu-miR-199b-3p inhibitor or shRNA-circ_NLRP1 was introduced.…”
Section: Discussionmentioning
confidence: 99%